(3GdfXQjI GdYGeI ddHWdGf ai GdbHV hGdJaJjT (B/ s - (3Ydi cGed GMeO MSjfs; (3GMeO YhV HdGds; (3eOMJ YHOGdMdje QeVGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3EPG cGfJ MeGjI Mbhb GdaQO GdCSGSjI aj GdMQjI hMQeI ecfg gj CYR CeGfj cd aQO hcGfJ ELQGAGJ GdbHV hGdJaJjT gj CcKQ GdELQGAGJ eSGSkG gPg GdMQjGJ , abO MQUJ GdCfXeI GdELQGFjI Ydi EMGWI GdbHV hGdJaJjT HSjGLkG ef GdVhGHW hGdVeGfGJ MQUkG efgG Ydi YOe GdeSGS HgPg GdZGjI, hef Ke abO MQUfG ef LGfHfG Ydi GdJCcjO Ydi Cf EZaGd gPg hJdc gh GdeONd Edi JbQjQ HWdGf ELQGAGJ GdbHV hGdJaJjT heG jJQJH YdjgG ef BKGQ ShGA cGf Pdc efUHkG Ydi Odjd GdHQGAI Ce GdEOGfI hShGA cGf Pdc aj Xd GdXQha GdYGOjI Ce GdGSJKfGFjI hHMSHGf Cf GdYdGbI hKjbI Hjf gPg GdCehQ heHOC GdeTQhYjI hef Ke aEf GdENdGd HPdc jDOi Edi GdENdGd HZGjI GdJhGRf Hjf eUdMI GdeLJeY heUMI GdaQO hHGdJGdj cGf MQUfG Ydi JCcjO gPG GdeHOC aj cGaI GdXQha hGdCMhGd hEdG cGf GdHWdGf gh fgGjI GdeWGa heUjQ gPg GdELQGAGJ ZjQ Cf GdJMQjQ HHWdGf ELQGAGJ GdbHV hGdJaJjT hYdi GdQZe ef Cfg LRGA jfUH Ydi gPg GdELQGAGJ hGdELQGAGJ GdeQJHWI HgG EdG Cfg dG jRjd GdVQQ GdPj hbY Ydi GdaQO VMjI gPg GdELQGAGJ GdHGWdI hef Ke cGf GdJCcjO ef LGfHfG Ydi VQhQI EbQGQ eHOC eSFhdjI GdOhdI hGdJahjV Yf eNGdaI CMcGe GdbHV hGdJaJjT GdJj JbQQ HWdGfgG HGYJHGQ Cf Pdc HYO VeGfI MbjbI haYGdI hSjGLkG jMei Mbhb GdCaQGO hMQjGJges
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2007s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B761-782s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGfXeI GdGLQGFjIs; (3GdMQjGJs; (3GdbHV hGdJaJjTs; (3MGdGJ GdJdHSs; (3GdMUGfI GdOHdheGSjI s; (3GdMUGfI GdHQdeGfjIs; (3TQhW UMI GdfOHs; (3YOe GdbHhds; (3GdHWdGfs; (3GdXQha GdESJKfGFjIs; (3GdVHW GdbVGFjs; (3MGdI GdWDGQjs; (3GdeSFhdjI GdLfGFjIs; (3eMceI GdfbV GdeUQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs